Biografi Alvia Santoni : Dari Akademisi ke Politisi Tahun 1998 - 2023 - Veronika, Mutiara Rejani; Asri, Zul (Jurnal Kronologi, 2024)
This study aims to provide an overview of the life journey and contributions of Alvia Santoni, the Deputy Mayor of Sungai Penuh, from being an academician to becoming a politician, along with his influences and roles. The author is interested in selecting Alvia Santoni as the subject of this biography because throughout his career in academia and politics, he has made significant advancements in the field of education in Sungai Penuh, Kerinci. The method used in this research is the historical method, which consists of several stages including heuristic, source criticism, interpretation, and historiography. The results of this study indicate that Alvia Santoni is a figure from Pondok Tinggi District, Sungai Penuh City. Known as Antos, he began his career as an academician by teaching and working in the library at the Academy of Business Administration (A2N) Kerinci in 1998. Antos was actively involved in the establishment of the College of Economics (STIE) – SAK. For 21 years, Antos served as a lecturer at STIE – SAK and from 2017 to 2020, he served as the Chairman of STIE – SAK. Eventually, Antos assumed the position of Deputy Mayor of Sungai Penuh from 2021 to 2024. Throughout his career as an academician and politician, Antos played various roles for Sungai Penuh, Kerinci, particularly in the field of education.